Depression, anxiety, alexithymia and somatosensory sensitivity in patients with benign palpitation - ÇİNÇİN, AHMET ALTUĞ; KEPEZ, ALPER; ÖZBEN SADIÇ, BESTE; TİGEN, MUSTAFA KÜRŞAT; SAYAR, NURTEN; YANARTAŞ, ÖMER; ERGÜN, SERHAT (TAYLOR & FRANCIS LTD, 2017)
Objective: The aim of this study is to compare the frequency of depression, anxiety, alexithymia and somatosensory sensitivity in patients with benign palpitation with healthy controls. Method: Sixty-one patients with palpitation and 59 age-and sex-matched control subjects were enrolled. All study subjects were undergone thorough cardiac evaluation, and patients with palpitation also had echocardiography and 24-hour ECG monitoring to rule out significant arrhythmias, coronary artery disease and structural heart disease. All subjects were assessed by Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Toronto Alexithymia scale, Whiteley Index (WI) and Somatosensory Amplification Scale (SAS). Results: Patients with benign palpitation had significantly increased BAI, BDI, WI and SAS scores. Anxiety is the only independent predictor of benign palpitation (odds ratio = 1.12, 95% confidence interval = 1.05-1.19, p < 0.001). Conclusion: This study shows that patients with benign palpitation had increased anxiety levels and somatization disorders. So an integrated psycho-cardiological approach is needed in this special population.
Keywords: Palpitation; depression; anxiety; somatosensory sensitivity; alexithymia; SCALE; INVENTORY; SYMPTOMS